SME BUSINESS DEVELOPMENT STRATEGY: SWOT AND EFE-EFI ANALYSIS - Hatta, Iha Haryani; Riskarini, Dian; Ichwani, Tia (Jurnal Aplikasi Manajemen, 2018)
SME Business Development Strategy: SWOT and EFE-EFI Analysis. The purpose of this research is to determine the profile, condition, and model of Small and Medium Enterprises (SME) business development strategy. The study used 40 respondents selected in a multi stage. Research location in Gresik Regency East Java determined four villages by purposive as the sample unit. Each unit was randomly taken ten perpetrators of SMEs processing marine fish as respondents. Data were analyzed by SWOT and EFE-EFI analysis. The results explained that most SMEs are young and well educated. Most SMEs are not yet legal entities. The level of ability of SMEs in managing the business and the level of achievement of marketing performance is good. The model of SME's business development strategy is S-O. Hope that SME's are more optimizing their strengths to take advantage of opportunities that are as optimal as possible.